2019
DOI: 10.3390/electronics8070726
|View full text |Cite
|
Sign up to set email alerts
|

Wiener–Granger Causality Theory Supported by a Genetic Algorithm to Characterize Natural Scenery

Abstract: Image recognition and classification have been widely used for research in computer vision systems. This paper aims to implement a new strategy called Wiener-Granger Causality theory for classifying natural scenery images. This strategy is based on self-content images extracted using a Content-Based Image Retrieval (CBIR) methodology (to obtain different texture features); later, a Genetic Algorithm (GA) is implemented to select the most relevant natural elements from the images which share similar causality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Metaheuristic algorithms are a subset of computational intelligence. This kind of computing paradigm has attracted attention over recent decades because of the algorithms' simplicity, flexibility, and local optimum avoidance [12][13][14][15][16]. In particular, some of them play an important role not only in academic society but also in many other practical engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Metaheuristic algorithms are a subset of computational intelligence. This kind of computing paradigm has attracted attention over recent decades because of the algorithms' simplicity, flexibility, and local optimum avoidance [12][13][14][15][16]. In particular, some of them play an important role not only in academic society but also in many other practical engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu, Y. et al suggested an altered adaptive algorithm on block-compressive sensing (BCS) by using saliency and error analysis [22]. In [23], Benavides-Álvarez, C. et al implemented a new strategy called Wiener-Granger Causality theory based on self-content images extracted using a Content-Based Image Retrieval (CBIR) methodology, for classifying natural scenery images. A scale-invariant deep neural network model based on wavelets for single image super-resolution (SISR) was proposed by Sahito, F. et al [24].…”
mentioning
confidence: 99%